Quantifying Radiation Exposure From Intraoperative Computed Tomography in Traditionally Safe Operating Room Zones. Issue 5 (May 2021) - Ford, Amy; Hughes, Mitchell; Wojewnik, Bartosz
Abstract : Objectives: To quantify the amount of radiation exposure from a commercially available computed tomography surgical imaging system that occurs in areas of the operating room that are generally believed to be safe and to correlate these amounts with established safety recommendations. Design: Experimental in vitro study. Setting: Standard hospital operating room at a Level 1 trauma center. Participants: Radiation survey instruments at specified distances from an intraoperative computed tomography scanner. Represented positions were the location of the anesthesiologist (80 cm), the radiation technologist (180 cm), the substerile room (500 cm), the operating room door (600 cm), the next-room nursing station (960 cm), and the hallway (1000 cm). Intervention: Radiation survey instruments were systematically exposed by a protocol intended to imitate expected radiation scatter during operative room use. Main Outcome Measurements: Radiation exposure readings from radiation survey instruments. Results: The mean radiation exposure rates are reported. The mean exposure rate was highest at the anesthesiologist (2200 mrem/h), followed by the door (25.33 mrem/h), the technologist (21.0 mrem/h), the substerile room (8.2 mrem/h), the hallway (2.633 mrem/h), and then the next-room nursing station (1.557 mrem/h). The mean integrated doses per scan were 15.03 mrem for the anesthesiologist, 0.170 mrem for the technologist, 0.136 mrem at the door, 0.033 mrem in the substerile room, 0.014 mrem in the hallway, and 0.005 mrem at the next-door nursing station. The exposure was related both to distance from the machine and to orientation from the machine. Conclusions: These results indicate that although there is measurable radiation exposure outside of the operating room, the magnitude is low enough to be clinically insignificant. This study provides data that reinforce the need to wear a protective gear or leave the room during the use of intraoperative computed tomography but unsuspecting surrounding staff need not worry about uninformed exposure.